A TOPSIS Framework for Supplier Selection Problem - Menarianti, Ika; Khoiry, I'tishom Al; Fathurachman, Chadyan (Jurnal Inovtek Polbeng Seri Informatika, 2024)
The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) stands as a widely recognized and extensively utilized method for addressing the complexities of supplier selection across diverse industries. Acknowledged for its systematic framework, TOPSIS serves as a valuable aid for decision-makers in meticulously evaluating and ranking potential suppliers, taking into account a variety of criteria. This paper provides a exploration of the TOPSIS framework in the field of supplier selection, aiming to empower decision-makers with insights to effectively utilize TOPSIS as a strategic tool. The objective is to facilitate informed and optimal supplier selections. The findings can contribute to both theoretical understanding and practical guidance, emphasizing the strategic significance of TOPSIS in decision-making.